Improved arterial spin labeling method: Applications for measurements of cerebral blood flow in human brain at high magnetic field MRI - Jahng, Geon-Ho (2007)
Measurements of cerebral blood flow (CBF) with arterial spin labeling (ASL) MRI are challenging primarily due to a poor signal-to-noise (SNR) ratio. Therefore, methods that improve SNR and minimize measurement errors can play a significant role for better estimations of CBF. The purpose of this work was to develop an ASL method for measurements of CBF at high magnetic field strength. In the proposed multislice ASL method, using in-plane double inversion for labeling, stationary spins are kept at equilibrium to avoid T(1) relaxation effects, while blood water is labeled using a lower magnetic field gradient. Improvement for CBF measurements is demonstrated on subjects and by comparison with other multislice ASL MRI methods at 1.5 Tesla. Furthermore, echo-planar imaging (EPI) and Turbo-FLASH (TFL) at 4 T MRI are compared for mapping CBF in human brain using various postlabeling delay times. CBF maps were obtained and analyzed within region-of-interests encompassing either gray matter or white matter. Elimination of T(1) dependence of stationary spins in conjunction with avoidance of magnetization transfer mismatch between labeling and control scans lead to improved CBF measurements. Although measurements of CBF in brain tissue are feasible at 4 T using either EPI or TFL, TFL reduced contaminations from an intravascular signal and susceptibility-related artifacts, providing overall more robust CBF measurements than EPI. Therefore, the proposed ASL method in combination with TFL should be used for measuring CBF of human brain at 4T.